Analysis of Spiritual Needs Using The Islamic Spiritel Mobile Application For Cancer Patients at Arifin Achmad Riau Hospital (HEALTH CARE: JURNAL KESEHATAN, 2026)
Cancer is a life-threatening disease that affects not only the physical condition but also the psychological, social, and spiritual aspects of patients. Spiritual needs are an important component in holistic health care. The use of mobile applications provides an opportunity to assess and identify patients' spiritual needs more effectively. The purpose of this study was to analyze the spiritual needs of cancer patients using mobile applications. This research method used a descriptive quantitative design. The study sample was patients with cancer who met the inclusion criteria. Data collection was carried out using a spiritual needs assessment instrument based on the SpiriTel mobile application. Data analysis was carried out descriptively by presenting frequency distributions and percentages. The results showed that most cancer patients were aged 23–60 years, female, had a high school education, and worked as housewives. The results showed that most cancer patients had high spiritual needs with mobile applications, namely 56.7%, while the other 43.3% had low spiritual needs. These findings indicate that spiritual needs are still an important aspect felt by patients during the process of cancer treatment and care, so that the fulfillment of spiritual needs needs to be integrated into holistic nursing services. The use of mobile applications can be an effective means to identify and facilitate the fulfillment of the spiritual needs of cancer patients, which is ultimately expected to improve the quality of life and well-being of patients.